Object oriented modeling of piston engines - Barros, José Eduardo Mautone; Valle, Ramón Molina; Da Silva, Paulo Sérgio [UNESP] (SAE International, 2001)
This work reports a conception phase of a piston engine global model. The model objective is forecast the motor performance (power, torque and specific consumption as a function of rotation and environmental conditions). Global model or Zero-dimensional is based on flux balance through each engine component. The resulting differential equations represents a compressive unsteady flow, in which, all dimensional variables are areas or volumes. A review is presented first. The ordinary differential equation system is presented and a Runge-Kutta method is proposed to solve it numerically. The model includes the momentum conservation equation to link the gas dynamics with the engine moving parts rigid body mechanics. As an oriented to objects model the documentation follows the UML standard. A discussion about the class diagrams is presented, relating the classes with physical model related. The OOP approach allows evolution from simple models to most complex ones without total code rewrite. Copyright © 2001 Society of Automotive Engineers, Inc.
Keywords: Class diagrams; Engine components; Environmental conditions; Flux balance; Global models; Momentum conservation equations; Motor performance; Moving parts; Objectoriented modeling; Physical model; Piston engines; Rigid body mechanics; Zero-dimensional; Ordinary differential equations; Runge Kutta methods; Torque motors; Engine pistons